TEACHING NARRATIVE WRITING BY USING ANIMATED MUSIC VIDEO FOR TENTH GRADERS - Nawa, Friska Maulita Yulfatul; Wahyuni, Sri; Aini, Nurul (Jurnal Pendidikan Bahasa Inggris Proficiency, 2024)
The aim of this study was to evaluate the efficacy of teaching writing to EFL students attending SMA Negeri 1 Plosoklaten using animated movies. This study is quantitative in nature. Participants in the research included 71 students from two courses. 36 students from the control group, X-IPA 3 SMA Negeri 1 Plosoklaten, and 35 students from the experimental group, X-IPA 2. Tests called pretests and posttests are used to gather data. The experimental group's average score of 81.74 and the control group's average score of 79.56, which were determined using ANCOVA, clearly showed that there was a significant difference between the two groups. According to the calculations, students in the experimental classrooms that used animated music video instead of image series for instruction had higher grade point averages. Because the significant value was 0.002 less than 0.05, the results indicated that the alternative hypothesis was accepted and the null hypothesis was rejected. This animated film serves as an effective training tool for the composition of narrative texts.